Biophysics and economic potential analysis of vertisols for maize in the humid tropics of Indonesia. (May 2018) - Neswati, R; Lopulisa, C; Ahmad, A; Nathan, M
Abstract: The main objective of this study is to establish the potential of Vertisols both biophysical and economic found in the humid relatively dry tropics region in the southern part of Sulawesi to the development of maize. This study used a spatial approach for establishing research sites totalling in 3 observations units of soil profile and involved 30 farmers as respondents. Land potential analysis of was conducted using parametric approach while economic analysis using the benefit-cost (B-C) ratio. The results show that the growing period of the study sites was in November to June, or 240 days and classified as climate type E3. The locations potentially moderately suitable or S2s for maize with soil texture as limiting factors in the growing season from November to June. In the growing season from July to October, the locations are not suitable or Nc with limiting factors such as very limited rainfall in the period of crop ripening. Land suitability Index of study site during the growing season from November to June ranged from 52 to 72 with an average productivity of maize obtained by farmers ranged from 4.3 to 5.7 tons of dry grain per hectare. Analysis of B-C ratio indicates that cultivation of maize in the growing period at such study locations are feasible with the value of B-C ratio ranged from 1.8 to 2.5. These results show that Vertisols in the humid tropics of Indonesia are physically and economically potential for maize development.